Comparing the Survival Outcomes of Radical Prostatectomy Versus Radiotherapy for Patients With De Novo Metastasis Prostate Cancer: A Population-Based Study - Guo, Xiaoxiao; Xia, Haoran; Su, Xiaonan; Hou, Huiming; Zhong, Qiuzi; Wang, Jianye (Frontiers in Oncology, 2021)
Purpose: The efficacy of local treatments (LTs) in selected patients with metastatic prostate cancer (mPCa) had been demonstrated. However, the comparative effectiveness between LTs is unclear. Here, we compared the impact of radical prostatectomy (RP) and brachytherapy (RT) on the survival outcomes of mPCa patients. Materials and Methods: mPCa patients received RT or RP between 2004 and 2016 were identified from the Surveillance, Epidemiology, and End Results database. Multivariable Cox proportional hazard analysis was used to evaluate the comparative risk of prostate cancer-specific mortality (CSM) and all caused mortality (ACM) between LTs. 1:1 propensity score matching (PSM) and adjusted standardized mortality ratio weighting (SMRW) were performed to balance the clinicopathological characteristics of groups. Results: Of 684 mPCa patients, 481 underwent RP and 203 received RT. After PSM, both groups included 148 cases and RT resulted in comparable CSM versus RP (CSM: hazard ratio [HR] 0.77, P = 0.325; ACM: HR 0.73, P = 0.138), which was consistent in the SMRW model (CSM: HR 0.83, P = 0.138; OS: HR 0.75, P = 0.132). However, RP associated with lower CSM in T1-2 subgroup (HR 0.42, P = 0.048) and lower ACM in T1-2 (HR 0.55, P = 0.031) and PSA≤20ng/ml (HR 0.48, P = 0.022) subgroups. Besides, the results showed that mortality risk was similar between the 2 groups in T3-4, GS > 7, PSA > 20 ng/ml and all metastatic subgroups (all P >0.100). Conclusions: RP could confer better survival outcomes than RT in mPCa patients with favorable primary tumour features, but not in those who with advanced primary tumour features. Moreover, the metastatic substage has limited impact on the comparative effectiveness between RP and RT. Further clinical trials are necessary to confirm the present results.